MALIGNANT PHYLLODES TUMOUR OF THE BREAST - Badar, Farhana; Mahmood, Shahid; Syed, Aamir Ali; Siddiqui, Neelam (Journal of Ayub Medical College Abbottabad, 2012)
Background: Malignant Phyllodes Tumour (MPT) is considered to be a rare disease of the breast. The most frequent clinical presentation of a MPT is a rapidly growing breast lump. Methods: Consecutive cases of MPT registered between Jan 1, 1995 and Dec 31, 2012 at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, were reviewed, to obtain information on age, tumour size, treatment given, disease-free survival, and overall survival. Disease-free survival was computed between the dates of surgery and recurrence, whereas, the overall survival time between the dates of diagnosis and last contact, both in months. Results: A total of 101 cases of Phyllodes tumour were recorded. These included: malignant tumours (42) benign (27), and borderline (32). Malignant Phyllodes tumours (42 cases) were studied further and 41 included for additional analysis. The mean age of the women in the study was 40.3±12.5 (22-72 years). Of the 33 patients who were disease-free after surgery, 15 had a recurrence, whereas, 18 did not have a recurrence. In those who had surgery alone versus those who received radiation treatment in addition to surgery, the median disease-free survival was 117 and 44.2 months, respectively. The mean overall survival time was 33.7 months. Conclusion: In this study, patients presented at a younger age than in other studies. Further exploration into molecular, biologic, geographic, and socioeconomic factors is needed to clearly understand the epidemiology of this disease in our population. Keywords: Phyllodes tumour, age, recurrence, breast cancer, women, Pakistan